Discriminate and indiscriminate use of amoxicillin and its effects on hematological parameters of broiler - Islam, Md Shakil; Islam, Md Zahorul; Islam, Md Shafiqul (Asian Journal of Medical and Biological Research, 2019)
Hematological indication is an important finding for pathophysiology analysis of biological science. This study was designed with the aim to investigate the effects of residual antibiotics on hematological parameters of broiler following discriminate and indiscriminate use. Broiler chicks were reared accordingly upto 30 days and on day 14 the chicks were randomly divided into 3 groups (n=6) namely control (group A), discriminate (group B) and indiscriminate (group C). At the age of day 16, amoxicillin treatment was started and continued for seven (7) days for in discriminate group (Group B) and fifteen (15) days for indiscriminate group. In case of discriminate group withdrawal period was properly maintained as nomenclature (Seven days) whereas, there was no withdrawal period in case of indiscriminate group. The hemoglobin (gm%) of control, discriminate, and indiscriminate group was 7.07±0.099, 6.97±0.095, and 6.90±0.124; Total erythrocyte count (TEC) 2.55±0.044 million/mm3, 2.53±0.038 million/mm3, and 2.50±0.026 million/mm3; Packed Cell Volume PCV (%) 19.83±1.302, 19.33±1.054, and 18.50±0.764 respectively. There was no significant difference on blood parameter found among the groups. Therefore, discriminate and indiscriminate use of amoxicillin has no bad effect on hematological parameters of broiler. Asian J. Med. Biol. Res. June 2019, 5(2): 153-157